STUDENTS' PERCEPTION TOWARDS CULTURAL COMPONENTS IN ENGLISH TEXTBOOK ENTITLED ‘WHEN ENGLISH RINGS A BELL’ - Sandra Dita S. (English Education Department Slamet Riyadi University Surakarta, 2021)
Textbooks were one of the supporting materials for learning. The textbook that was chosen by the teacher has a very big role for students. This can be proven through student learning outcomes in understanding foreign language materials related to culture. That was why researcher conducted research on students' perceptions of understanding the cultural components contained in an English textbook entitled When English Ring a Bell. The purpose of this research was to determine students' perceptions towards cultural component in English textbooks. In this research, the researcher was used descriptive qualitative research. Subject of this research is students of VIII grade SMP Advent Surakarta. This research was used descriptive qualitative and the data were obtained by interviewing English teacher and questionnaires consists of 49 questions that were distributed to the students via Google Forms. The results of the interview with English teacher regarding students' understanding of the use of cultural components in English textbooks indicate that students need to be directly involved in practicing the material in the textbooks, so that students better understand the material even though some students lack of speaking and pronouncing skill. The results of the questionnaire show that students' perceptions of understanding the use of cultural components through textbooks were supported through the role of the teacher, the display design of textbooks and materials that are easy to understand, but not optimal, this is due to the use of additional learning media other than textbooks. Keywords: Student perception, cultural components, English textbook